WORK FROM HOME DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN KANTOR INSPEKTORAT KOTA YOGYAKARTA - Anggelina, Riska; Chasanah, Uswatun (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The purpose of this study is to examine the effect of Work from Home (WFH) and Job Satisfaction on the Work Productivity on Employees at Yogyakarta City Inspektorat. Data collection was done by survey method on 67 employees. Data processing was done using SEM-PLS program. Evaluation of the measurement model (outer model) with reflective indicators was evaluated by three criteria, convergent validity, discriminant validity and composite reliability. Convergent validity and discriminant validity showed that all constructs are valid, both the AVE value and the outer loading value > 0.70, while the composite reliability showed that all constructs have a composite reliability value > 0.70. The results showed that Work from Home (WFH) with job satisfaction as a mediator has a positive and significant effect on work productivity. This can be proven by the value of t statistic > 1.96 with a value of 4.358 > 1.96 and p value < 0.05 with a value of 0.000 < 0.05. So it can be concluded that Work from Home (WFH) with job satisfaction as a mediator can increase work productivity. There are two important implications in this research, first, for Inspektorat, it is necessary to regulate fair and transparent management of Work from Home (WFH) and Work from Office (WFO) so that there is no feeling of unfair treatment from employees which will affect employee satisfaction. Second, for employees to be able to maintain a balance between office and home work so that work productivity continues to increase.